Sustainable Healthcare Infrastructure Performance Metrics for Long Term Asset Management and Value Creation - AbuYusuf Aminu-Ibrahim; John Chinemerem Ogbete; Obinna Chima Iwuanyanwu (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Sustainable healthcare infrastructure requires performance metrics that extend beyond initial capital delivery to support long term asset management, service continuity, and public value creation. This study examines the development and application of sustainability oriented performance metrics for healthcare facilities across their operational life cycle. It integrates insights from infrastructure asset management, health systems planning, and sustainability science to propose a structured metric framework that aligns technical performance, financial stewardship, and social outcomes. The analysis emphasizes the limitations of traditional project focused indicators that prioritize cost, schedule, and short-term efficiency while neglecting operational resilience and lifecycle impacts. Key metric domains are identified, including asset condition and reliability, energy and resource efficiency, environmental emissions, patient safety, service accessibility, and workforce wellbeing. Financial metrics addressing lifecycle cost, maintenance optimization, and risk adjusted value preservation are examined alongside clinical and community outcome indicators. The study highlights the role of digital technologies in enabling continuous performance measurement. Building management systems, asset information models, and data analytics platforms are discussed as tools for real time monitoring, predictive maintenance, and evidence-based decision making. By linking operational data with governance and reporting structures, these tools support transparency, accountability, and informed reinvestment strategies. Sustainability metrics are positioned as decision support instruments rather than static reporting requirements. The framework emphasizes feedback loops that allow infrastructure managers to adapt asset strategies in response to changing demand, climate risks, regulatory expectations, and technological advances. Particular attention is given to aligning performance metrics with long term health system goals, including equity, resilience, and carbon reduction commitments. Overall, the abstract argues that sustainable healthcare infrastructure performance metrics are essential for transforming assets from cost centers into strategic enablers of health system value. By embedding lifecycle oriented, multidimensional metrics into asset management practice, healthcare organizations can improve reliability, optimize resource use, and protect public investment over time. The proposed approach provides practical guidance for policymakers, facility managers, and investors seeking to enhance long term asset performance, fiscal sustainability, and societal value creation within complex and resource constrained healthcare environments globally, across diverse institutional contexts and evolving demographic, economic, and epidemiological conditions worldwide sustainably.